Developing a rapid access chest pain clinic: Qualitative studies of patients' needs and experiences - Price, J; Mayou, R; Bass, C; Hames, R; Sprigings, D; Birkhead, J (2005)
Objective: The aims of this study are to understand the needs and experiences of rapid access chest pain clinic attenders and to determine the acceptability and effectiveness of simple procedural changes. Methods: Two qualitative studies of clinic attenders before and after procedural changes which were guided by the first study. Results: Study 1: Patients wanted to be reassured, by knowing what was causing their pain, understanding the cause, and feeling able to help themselves. Often, these needs were not met, and uncertainties left some patients feeling ill-equipped to help themselves. Communication problems were identified. Study 2: The changes were acceptable to patients, and almost all were reassured. Most valued receiving extra verbal and written advice and information. Many felt more aware of cardiac risk factors and intended to change their lifestyle. Conclusion: There were clear opportunities for improvements in care. Changes in procedures helped patients to understand their pain, to practice self-management, and to consider altering their lifestyle. © 2005 Elsevier Inc. All rights reserved.